A Syntactic Analysis of Noun Phrase in Pride and Prejudice Novel by Jane Austen - ASTUTI , ZAKIYAH WASNADI (2007)
This study is about a phrase in English, especially the English noun phrase in the novel Pride and Prejudice by Jane Austen. Noun phrase is a phrase which has a noun as a head and consists of a noun and all the words that modify it. The objectives of this research are: 1) to identify the modifiers of English Noun Phrase used in the Pride and Prejudice novel, and 2) To describe the distribution of the modifiers of noun phrase in the Pride and Prejudice by Jane Austen. This research is descriptive qualitative research that describes the English noun phrase modifier and its distribution in a sentence. This research is concentrated on grammatical structure with applying the syntactic structure of modification to analyze the data by using Chinese box. The data are English noun phrases collected by using observation. The results of the research are: 1) there are six modifiers of English noun phrase. They are: a) adjective/adjective phrase, b) noun, c) prepositional phrase, d) infinitive, e) adverb, f) clause. 2) Based on the position, there are three positions of modifiers, those are, a) pre-position (before N), post-position (after N), and c) before and after N.